VARIATION IN INTERNAL CAROTID ARTERY PROTRUSION AND DEHISCENCE IN A SUBSET OF KARACHI POPULATION - Mubina Lakhani; Iffat Raza; Maria Mohiuddin; Rosheena Nabeel Khan; Santosh Kumar Sidhwani; Nuzhat Hassan (Journal of Rawalpindi Medical College)
Objective: To find out the frequency of protrusion of Internal Carotid artery in sphenoid sinus and dehiscence of carotid canal in a subset of Karachi population.